Washington Irving’s Satirical Works: Folk Life And Social Issues (Zien Journal of Social Sciences and Humanities, 2026)
This article analyzes the satirical interpretation of historical events in the works of the American writer Washington Irving. In his writings, the author highlights social and cultural processes through humor and irony, offering a critical perspective on the issues of his time. The study examines Irving’s use of satirical devices, his artistic expression, and his skill in portraying historical events in a vivid and imaginative way. Furthermore, the article explores how social shortcomings and human traits are revealed through satire, supported by relevant examples. The paper aims to identify the literary and cognitivelinguistic aspects of Irving’s творчество